Identification of Diversity Macrobenthos as a Bioindicator of Seawater Quality in Teluk Dalem Beach and Senggigi Beach - Rachmawati Noviana Rahayu; Immy Suci Rohyani; Ahmad Jupri; Dela Savira; Feby Ayu Genggelang; Risma Indriana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Macrobenthos are organisms that live on the bottom of the waters have the characteristics of slow life movement and can survive for a long time so that they have the ability to respond to changes in the quality of a water. One way to determine the quality of seawater as a bioindicator of the stability of an ecosystem is to know the macrobenthos diversity index. This research aims to identify factors that influence the diversity of macrobenthos abundance on the coast of Teluk Dalem and Senggigi coast,and then to analyze the role of macrobenthos as a bioindicator of seawater quality on the coast of Teluk Dalem and Senggigi beach. The method used in this study is quantitative descriptive method. The results showed that the abundance of macrobenthos on the coast of Teluk Dalem and Senggigi beach had a relatively good diversity index, it is influenced by the physical, chemical and biological conditions of the environment.